The Influence of Brand Ambassador and Product Quality Toward Repurchase Intention Mediated by Customer Satisfaction of Lemonilo Brand Instant Noodle Products: The Influence of Brand Ambassador and Product Quality Toward Repurchase Intention Mediated by Customer Satisfaction of Lemonilo Brand Instant Noodle Products - Yulia Rifka Nur Fathia; Jean Richard Jokhu (Lentera Ilmu Madani, 2023)
Lemonilo is a brand of instant noodles marketed in Indonesia. Lemonilo is a fast food noodle made from organic spinach which is also flavored with selected ingredients that are free of preservatives and MSG. This study aims to determine the role of customer satisfaction and repurchase intention on brand ambassadors and product quality in purchasing Lemonilo Noodle products, and analyze what factors influence purchasing decisions for Lemonilo Noodle products. Using the theory from Hair (2006), the number of respondents collected was 196 samples. The data obtained from the sample will be analyzed using Partial Least Square (PLS). PLS can build a proposition testing relationship as a confirmation of theory with one of the analytical techniques that provide statistical efficiency. From the results of hypothesis testing, it states that of the five hypotheses there are two hypotheses that are not accepted. So, it can be concluded that Brand Ambassador has no influence on Repurchase intention, Product quality has an influence on Repurchase Intention. Brand Ambassador has an influence on Customer Satisfaction and product quality has no influence on Customer Satisfaction and finally customer satisfaction has a significant influence on customer satisfaction.